1977
DOI: 10.1136/bmj.2.6080.156
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone, insulin, and prolactin secretion in anorexia nervosa and obesity during bromocriptine treatment.

Abstract: such complicating factors as variable absorption or distribution.Two important features emerge from this study. Firstly, our findings confirm observations'0"1 of an age-related decline in microsomal oxidation rates in man. Secondly, they show that in a population exhibiting this decline acetylation does not change with age. Thus, there are pharmokinetic grounds in the elderly for reducing the dose of drugs that are metabolised by oxidation, but this does not seem to apply to drugs metabolised by acetylation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This phenomenon is somewhat surprising since other findings suggest a reduction in the dopaminergic pool in AN (Mawson 1974). Significantly, some authors (Johanson and Knorr 1974) although not unanimously (Harrower et al 1977), have found an improvement of the disease in patients treated with dopaminergic drugs. In addition, Nomifensine, a new drug which inhibits the pre-synaptic re-uptake provokes a reduction of PRL in normal subjects (Laakman and Benkert 1978) but not in our cases Horm.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is somewhat surprising since other findings suggest a reduction in the dopaminergic pool in AN (Mawson 1974). Significantly, some authors (Johanson and Knorr 1974) although not unanimously (Harrower et al 1977), have found an improvement of the disease in patients treated with dopaminergic drugs. In addition, Nomifensine, a new drug which inhibits the pre-synaptic re-uptake provokes a reduction of PRL in normal subjects (Laakman and Benkert 1978) but not in our cases Horm.…”
Section: Discussionmentioning
confidence: 98%
“…(1) The occurrence of a paradoxical rise following oral glucose feeding (Alvarez et al, 1972;Casper et al, 1977;Franklin & Jenkins, 1972;Macaron et al, 1978;Vanderlaan, Parker, Rossman, & Vanderlaan, 1970), which is attenuated by bromocriptine (Harrower, Yap, Nairn, Walton, Strong, & Craig, 1977).…”
Section: Dynamic Testing Of Hch Releasementioning
confidence: 99%
“…No research has yet been done into this matter, but a few studies have obliquely re¬ garded body weight during treatment with dopa¬ mine agonists. A lack of effects on body weight was reported in obese women and women with anore¬ xia nervosa (12), and in patients with hyperprolac¬ tinemia (13,14). Nevertheless, weight loss during treatment with bromocriptine has been reported (15)(16)(17), and incidental cases of weight gain (13,18).…”
mentioning
confidence: 97%